The Congregational Reaction to the Phenomenon of Laroma Organization - Lantang, Alfa Syeevert; Tewu, Matulandi Arthur; Tamaweol, Roy Dekky; Tombeng, Ineke Marlien (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2025)
This study discusses the interaction between adherents of the Laroma organization beliefs who are still loyal to carrying out Minahasa old beliefs with the surrounding community. Where when believers perform their obligations as believers, there is an act of rejection accepted by believers. Through the approach of Christian theology and qualitative research methods, this study aims to understand the views or reactions of the congregation to the phenomenon of the existence of the laroma organization, and how they can coexist with every difference that exists. So as to create a good relationship that respects and respects each other in a plural life while maintaining the faith of Christian beliefs.